Application of Theory of Unpleasant Symptoms tRoad o Reduce Stress, Anxiety and Depression in Lung Cancer Patients - Rufli, Arza; Gayatri, Dewi; Hargiana, Giur (Teewan Solutions, 2025)
Lung cancer patients often face significant psychosocial distress, negatively impacting their quality of life. To address this problem and equip patients with coping skills, the application of the concept of Theory of Unpleasant Symptoms (TOUS) has become a relevant assessment format. Ten cases of lung cancer patients managed by the Resident showed that EvidenceBased Nursing Practice (EBNP) interventions in the form of Mindfulness Loving-Kindness Meditation (MLKM) were effective in treating psychological distress. This intervention has been shown to significantly reduce levels of stress, anxiety, and depression in patients. Therefore, MLKM is recommended as an essential nursing intervention to help lung cancer patients cope with their psychological distress. Oncology nurses are advised to adopt the TOUS approach in managing lung cancer patients experiencing psychological problems, strengthening evidence-based nursing practices in holistic governance. Keywords: Lung Cancer, Psychological Distress, Loving Kindness Meditation, Discomfort Theory.